Asymmetric volatility spillover between crude oil and other asset markets - Bo Guan; Khelifa Mazouz; Yongdeng Xu (Cardiff University, Cardiff Business School, 2023)
This study uses the Multiplicative Error Model (MEM) to explore asymmetric volatility spillovers between crude oil and other major asset markets. We have extended the MEM of Engle et al. (2012) and ddd to include asymmetric volatility spillovers and developed the spillover balance as well as asymmetric spillover indexes. We have then allowed these indexes to vary over time. Our results reveal that the stock market is the dominant contributor to volatility spillover, while the crude oil is mostly the volatility spillover recipient. The asymmetric spillover effects are predominantly negative in the stock and crude oil markets and positive in the bond market. We further show that the spillover indexes are dynamic and influenced by specific events, such as the global financial crisis and the COVID-19 pandemic, as well as varying economic conditions.
Keywords: G10; G15; C58; F36; 330; asymmetric volatility spillovers; global asset markets; Multiplicative Error Model (MEM); spillover balance index